Impact of Different Antiretroviral Strategies on Total HIV-DNA Level in Virologically Suppressed HIV-1 Infected Patients - Bon, Isabella; Calza, Leonardo; Musumeci, Giuseppina; Longo, Serena; Bertoldi, Alessia; D'Urbano, Vanessa; Gibellini, Davide; Magistrelli, Eleonora; Viale, Pier L.; Re, Maria Carla (Current HIV Research, 2017)
Background: Total HIV-DNA load in peripheral blood cell (PBMCs) reflects the global viral reservoir that seems not to be affected by antiretroviral treatment. However, some studies reported a different permeability of different drugs in cellular compartments. Objective: To investigate the relation between the amount of total HIV-1 DNA and different treatment strategies. Methods: Total HIV-1 DNA was quantified by real time PCR in PBMCs collected from 161 patients with long-term undetectable HIV-RNA receiving different therapy schedules (3-drug regimens or 2-drug regimen containing Raltegravir as integrase inhibitor). Results: Overall, HIV patients who started therapy with a median pre-ART CD4+ cell count >400 cells/mm3 and HIV viral load of 3 log10 copies/ml, achieved a lower amount of HIV total DNA. No significant correlation was found in DNA size when patients were stratified on the basis of different therapeutic protocols. However, HIV DNA load analysis, when only performed in HIV patients with a median pre-ART CD4+ cell count >200 cells/mm3 and HIV viral load < 3 log10 copies/ml, showed a significative DNA decrease in Raltegravir treated group with respect to the NNRTIs-treated group. Conclusion: The data emphasize that HIV-DNA level represents a predictive factor in long-term suppressive therapy patients. In addition, the diminished reservoir, only observed in patients treated with the NRTI-sparing regimen RAL plus PI/r before immunological and virological derangement, suggests that latest generation drugs, such as integrase inhibitors, might represent an optimal chance in the management of HIV infection.
Keywords: CD4+ cells